Anti-aging properties of metformin - Anna Małgorzata Łopuszyńska; Mateusz Pawlicki; Magdalena Kozioł; Aleksandra Krasa; Ewa Piekarska; Halina Piecewicz-Szczęsna (Kazimierz Wielki University, 2021)
Introduction: Life expectancy of human population is being constantly prolonged, hence there is a lot of research into drug that will prevent the effects of aging. There are many reports that metformin, which is a drug used in type 2 diabetes, has anti-aging effects. It belongs to the group of biguanides and has been used since the 1950s. It is a relatively safe, cheap and effective drug, which makes it a promising subject for many studies. The purpose of this review is to present the latest developments in this field.  Material and methods: PubMed scientific base was searched using following keywords: metformin, aging, anti-aging, in years 2017-2021.  Results: Numerous studies show that metformin has an impact on aging through the nutrient pathway, AMPK signaling pathway, and its effects on reactive oxygen species. In addition, it has an anti-cancer effect, inhibiting, among others, rectal cancer cells and p53 mutant colon cancer. Research in rodents has shown that this<span class="TextRun SCXW48609226 BCX0" lang="EN-US" xml:lang="EN-US"